Prescriptions for punishment: Official ideologies and jall overcrowding - Pontell, Henry N. (American journal of criminal justice, 1989)
This study assesses key actors’ “worlds of fact” regarding jail overcrowding in California through an examination of their perceptions of causes and effects, support for different solutions, and adherence to major punishment ideologies. How policymakers define and structure a specific problem Gail overcrowding), can influence how policy options are differentially weighed as well as how existing policy processes can be improved. A mail survey was sent to two key decision making groups who largely regulate the intake and outflow of local jails: sheriffs and chief probation officers of the 58 California counties. Group differences in responses were predicted from the perspectives of blame avoidance, domain dissensus, and punishment theory. Relationships were examined among perceived causes, effects, solutions, and punishment ideologies. While both sheriffs and probation chiefs advocated highly similar “control-oriented” punishment ideologies, probation chiefs advocated more “progressive” solutions to jail overcrowding. Perceived causes and effects of jail overcrowding, along with support for deterrence ideology, were strongly related to elite support for three potential solutions: building more institutions, passing tougher laws to deter potential offenders, and using shorter sentences for low-risk offenders. Implications of these results for understanding jail overcrowding and policy processes are discussed.